Anna Freud Gedichte. Prosa. Übersetzungen. - Spreitzer, Brigitte (2014)
Brigitte Spreitzer makes Anna Freud's literary texts fully accessible in this book for the first time. The detailed preface contextualises Anna Freud's literary texts as paradigmatic sources, which are documenting the engagement of a young Austrian Jewish middle class woman with socio-historical and cultural conditions in Fin de siècle Vienna.